PROFITABILITY OF LOCALLY MILLED RICE MARKETING IN CENTRAL ZONE OF GOMBE STATE, NIGERIA - Adam, A.A.; Ya’u, A.; Bala, T.; Jaafar, I. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to analyse the profitability of locally milled rice marketing in Central Zone of Gombe State, Nigeria. A multi-stage sampling technique was used to arrive at the sample size for the study. Data for the study were collected using a semi-structured questionnaire and analysed using descriptive and inferential statistics. The result revealed that the mean age of the respondents was 45.61 years, 85.9% of the respondents were male, 84.2% were married and 76.6% had at least primary education. Mean marketing experience was 17.6 years and mean household size was 9 persons. The result further revealed that most (81.5%) of the respondents belonged to marketing association and 84.8% had no access to formal sources of credit. The cost and return analysis of marketing 100kg bag of locally milled rice showed that purchase cost (N135,913.04) was the most important cost component constituting 97.94% of total marketing cost, followed by cost of transportation (N1,084.78), handling (N631.58), Storage (N600.22), loading and off-loading (N391.3) and tax (N145.90) constituting 0.78%, 0.43%, 0.46%, 0.28% and 0.11% of total cost respectively. Total cost of marketing services (CMS) was N2,853.78. The gross revenue, gross margin, marketing margin and marketing efficiency of marketing 100kg bag of locally milled rice were N144,497.55, N5,730.73, 3.97% and 483.11% respectively. Inadequate capital, inadequate credit facilities, price fluctuations and transportation were the major problems affecting locally milled rice marketing in the study area ranked 1st, 2nd, 3rd and 4th respectively. The study concluded that locally milled rice marketing is a profitable enterprise in the study area. It is therefore recommended that Government and financial institutions provide financial windows for marketers to easily acquire credit, marketers should leverage on existing market associations to demand necessary market facilities such as storage facilities from concerned authorities and Government should open up and rehabilitate rural roads to ease transportation and improve marketing efficiency.